2022
DOI: 10.3389/fpubh.2022.901686
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Emotion Regulation Strategies in the Relationship Between Big Five Personality Traits and Anxiety and Depression Among Chinese Firefighters

Abstract: Identification of protective factors to prevent firefighters' anxiety and depression is meaningful. We explored whether emotion-regulation strategies mediate the relationship between personality traits and anxiety and depression among Chinese firefighters. Approximately, 716 Chinese firefighters were recruited and completed the Emotion Regulation Questionnaire (ERQ), Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), and Big Five Inventory−2 (BFI-2) Scale. Results (N = 622) indicated that onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
1
12
0
1
Order By: Relevance
“…The total score was calculated by the sum of the scores for each item, and the standard score of this scale was utilized to measure anxiety levels (standard score = total score * 1.25 and rounded to the nearest whole number). Previous studies have shown that the scale had excellent reliability and validity (Tao et al,2022). The Cronbach alpha coe cient for this scale in this study was 0.853.…”
Section: Measurement Of Anxietysupporting
confidence: 58%
“…The total score was calculated by the sum of the scores for each item, and the standard score of this scale was utilized to measure anxiety levels (standard score = total score * 1.25 and rounded to the nearest whole number). Previous studies have shown that the scale had excellent reliability and validity (Tao et al,2022). The Cronbach alpha coe cient for this scale in this study was 0.853.…”
Section: Measurement Of Anxietysupporting
confidence: 58%
“…Furthermore, our study showed that EI mediated the association between openness to experience and depression/anxiety, in line with previous studies [ 42 , 43 ]. For instance, individuals with high scores of openness to experience use more communication to enhance positive emotions and regulate negative emotions [ 44 ]. In parallel with being open to new experiences, emotionally intelligent medical students know how to handle their own and others’ emotions and how to deal with emotions effectively, which leads to a better adaptation to the demands and challenges of the medical program.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional regulation refers to the abilities or coping strategies to effectively address psychological distress based on cognitive and behavioral tactics (Tao et al, 2022 ). Individuals' affective states are remarkably modulated by emotional regulation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a long-term and recurrent rumination is assumed to cause an increase in negative affect in adolescents (Park et al, 2004 ). Emotional regulation insufficiency or inappropriateness was also found to be associated with a plethora of mental disorders, such as depression, anxiety, and suicidal ideation (Marganska et al, 2013 ; Brausch and Woods, 2019 ; Tao et al, 2022 ). Emotion regulation capacities are also critically important for the improvement of adolescents' emotional experience and their accommodation with socio-emotional stressors (McLaughlin et al, 2011 ; Ma and Fang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation